Anne Riising, Aage Fasmer Blomberg, Ellen Pedersen, Hans Henrik Jacobsen: Odense Katedralskoles Historie 1282-1983. (Odense Universitetsforlag, 1984). 417 s. ill., 198,-kr. - Bonderup, Gerda (Historie/Jyske Samlinger, 1987)
-